The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.7589/0090-3558-48.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Puumala Virus Infection on Maturation and Survival in Bank Voles: A Capture-Mark-Recapture Analysis

Abstract: ABSTRACT:Many zoonotic diseases are caused by rodent-borne viruses. Major fluctuations in the transmission of these viruses have been related to large changes in reservoir host population numbers due to external factors. However, the impact of the pathogen itself on the demography of its reservoir host is often overlooked. We investigated the impact of Puumala virus (PUUV) on survival and reproductive maturation probability of its reservoir host, the bank vole (Myodes glareolus). Three years (2004-06) of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 37 publications
(46 reference statements)
0
32
1
1
Order By: Relevance
“…Such complex relationships between parasite infection and host fitness were indeed observed in other rodent-borne diseases. For example, infection of Puumala hantavirus in bank voles ( Myodes glareolus ) was initially assumed to be asymptomatic [5153] but recent long-term field studies observed negative effects on the survival probability and an equivocal impact on the fecundity of females [36, 54, 55]. An important difference between Old World arenaviruses and hantaviruses, however, is that the latter causes persistent infections in their reservoir hosts [56], while the former infects their hosts mainly acutely [29, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Such complex relationships between parasite infection and host fitness were indeed observed in other rodent-borne diseases. For example, infection of Puumala hantavirus in bank voles ( Myodes glareolus ) was initially assumed to be asymptomatic [5153] but recent long-term field studies observed negative effects on the survival probability and an equivocal impact on the fecundity of females [36, 54, 55]. An important difference between Old World arenaviruses and hantaviruses, however, is that the latter causes persistent infections in their reservoir hosts [56], while the former infects their hosts mainly acutely [29, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Selection acting on Tnf promoter could therefore be linked to PUUV, either indirectly, or potentially directly. Indeed, several ongoing studies are providing evidence of negative effects of PUUV on different components of vole fitness, including survival [28,29,71] . …”
Section: Impact Of Immunity-related Genes On the Risk Of Hantavirumentioning
confidence: 99%
“…In rodents, which are the reservoirs of pathogenic hantaviruses, infection is persistent [26,27] and mainly asymptomatic but see [28,29,30]. Nevertheless rodents differ in their probability of being infected with their associated hantavirus e.g., [31].…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of aerosolized rodent excreta is also considered the main route of infection to humans (Hjelle & Glass, 2000;Vapalahti et al, 2010). No apparent symptoms have been reported in rodent hosts due to hantavirus infection, but it may impair host survival in nature (Kallio et al, 2007;Luis et al, 2012;Tersago et al, 2012). The hantavirus infection induces a life-long antibody response where IgG appears in the bloodstream 2 to 3 weeks after infection, but viral RNA and/or infectious virus is found in various tissues, especially in the lungs of chronically infected animals (Botten et al, 2003;Hardestam et al, 2008;Meyer & Schmaljohn, 2000;Schountz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%